2022
DOI: 10.3390/ani12212968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Livestock Grazing on Spatio-Temporal Patterns and Behaviour of Reeves’s Pheasant Syrmaticus reevesii

Abstract: Protected areas are seeing an increase in anthropogenic disturbances in the world. Previous studies have demonstrated the impact of livestock grazing and human presence on the habitat use of birds, whereas little is known about the effect of free-ranging livestock on bird behaviour. Reeves’s Pheasant (Syrmaticus reevesii) is endemic to China and has been threatened by habitat loss and fragmentation, illegal logging, and human disturbance over the past 20 years. Based on camera trapping in the Liankangshan Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Feral donkeys in the study area traveled in herds averaging 10 animals throughout the area, rather than along tracks or paths, distributing their impact throughout large areas. Previous studies have shown that livestock grazing may strongly affect birds, influencing their activity patterns, distribution, abundance, and/or nest success [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Feral donkeys in the study area traveled in herds averaging 10 animals throughout the area, rather than along tracks or paths, distributing their impact throughout large areas. Previous studies have shown that livestock grazing may strongly affect birds, influencing their activity patterns, distribution, abundance, and/or nest success [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%